KERAGAMAN GENETIK Tacca leontopetaloides (L.) Kuntze (Taccaceae) DARI BEBERAPA PROVENANSI DI INDONESIA BERDASARKAN MARKA INTER SIMPLE SEQUENCE REPEATS (ISSR) - Marlina Ardiyani; Lulut Dwi Sulistyaningsih; Yunita Nur Esthi (BERITA BIOLOGI, 2014)
Kecondang or Taka (Tacca leontopetaloides), a member of Taccaceae, is one the carbohydrate alternatives to rice which can be developed in coastal area. With the global warming, the sea level has increased and small islands are more isolated. The people who lives in these islands should depend on their bioresources.As Taka inhabits coastal area, the development of this plant becomes critical.A total of 65 accessions of Taka from 9 provenances in Indonesia (Sukabumi, Madura, Kp.Siung (Yogyakarta), Gn. Kidung (Yogyakarta), and the small islands in Karimun Jawa namely Nyamuk, Katang, Cendekia, Kumbang, Seruni islands) were characterized using six ISSR markers [GSGG (TG5)T; CCAG(TGG)3TG; GGAG(TGG)3TG; BDBT(TCC4); (AC)8C; (AG)8G]. The scoring of the fragments resulted in 55 (69.6%) polymorphic bands. The size of the bands varied from 150bp to 1,6kb. The 65 accessions of Taka made several clusters according to their provenances. The range of individual genetic dissimilarity was from 0.012 to 0.186. The results showed that amongst nine population studied, Gn. Kidul, Yogyakarta population has the highest level of genetic variation with mean values of Na = 1.3544±0.4814, Ne =1.1784±0.3025, PLP = 35.44% and He = 0.1094±0.1681. Whereas, P. Nyamuk, Kep. Karimun Jawa population has the lowest level of genetic variation with mean values of Na = 1.0759±0.2666, Ne = 1.0523±0.2163, PLP = 7.59% and He = 0.0275±0.1097.